PENGARUH PENERAPAN STRATEGI PRACTICE REHEARSAL PAIRS TERHADAP HASIL BELAJAR MENGANYAM VAS BUNGA SISWA KELAS VIII SMP NEGERI 2 SUNGGGAL - Halida Hanim; Aulia Syafitri (Universitas Negeri Medan, 2017)
ABSTRACT The This study aimed to determine the differences in student learning out comes using strategi practice rehearsall pairs learning model with convention learning models in the competency of plaiting vase in grade VIII of SMP Negeri 2 Sunggal. The samples were two classes randomly selected. The first class in strtegi practice rehearsal pairs teaching used and second classs in convensional learning model. The instrument of data collection was the observation sheet. Data were analyzed using t-tes analysis technique. Based on the calculations, the value of t = 5,845 > t 1,669 at the 5 % significant level, the hypothesis which states that there was a significant difference in learning outcomes between the results of learning in plaiting vase using learning model strategi practice rehearsal pairs with conventional learning model on students grade VIII. Kata Kunci: Menganyam Vas Bunga, Strategi Practice Rehearsal Pairs